Validation of a lean smart maintenance maturity model - Maier, Hans Thomas (Array, 2020)
Rising complexity in industrial asset and maintenance management due to more volatile business environments and megatrends like Industry 4.0 has led to the need for a new perspective on these management domains. The Lean Smart Maintenance (LSM) philosophy, which focuses on both the efficient (lean) and the learning (smart) organization was introduced during the past few years, and a corresponding maturity model (MM) has been developed to guide organizations on their way to asset and maintenance excellence. This paper discusses use cases, in which the usability and the generic aspect of the LSM MM are validated by using data from three different asset management assessment projects in organizations with different types of production. Research results show that the LSM MM can be used as a basis for management system improvement, independent of production types such as one-of-a-kind industry, mass production and continuous production.